Fading With Time of PD-L1 Immunoreactivity in Non–Small Cells Lung Cancer Tissues: A Methodological Study. Issue 7 (August 2018) - Giunchi, Francesca; Degiovanni, Alessio; Daddi, Niccolò; Trisolini, Rocco; Dell'Amore, Andrea; Agostinelli, Claudio; Ardizzoni, Andrea; Fiorentino, Michelangelo
Abstract : Blockade of inhibitory immune checkpoints is currently arising as a potential immunologic option for tumor therapy. Inhibition of programmed cell death protein 1 and/or its specific ligand programmed death-ligand 1 (PD-L1) was effective in clinical trials in advanced melanoma, non–small cell lung cancer (NSCLC) bladder and kidney cancer. The predictive role of the immunohistochemical (IHC) expression of PD-L1 is highly debated. Different reagents, clones, cutoffs of cell expression and subjective interpretation of PD-L1 immunoreactivity in epithelial cells and lymphocytes are the main issue. In this study we selected 58 consecutive NSCLC surgical specimens that underwent pathologic examination from January 2014 to July 2015. Using a tissue microarray approach we evaluated the IHC expression of PD-L1 in tumor-infiltrating lymphocytes and tumor cells (TCs) and compared the ICH staining with tumor histology, grade and the age of the tissue blocks. The main new finding was the fading of PD-L1 IHC expression in TCs in tissues processed in 2014 compared with 2015. PD-L1 expression in tumor-infiltrating lymphocytes in the 2 years was similar. We also found a significant higher immunoreactivity of TCs in high grade NSCLC and in the squamous carcinoma histotype compared with low grade tumors and the adenocarcinoma histology ( P =0.013). We demonstrated that the IHC evaluation of PD-L1 in NSCLC archival tissues is feasible and can be implemented in a routine pathology setting, but it should be carefully assessed in tissue blocks older than 1 year.